Experimental investigation and performance evaluation of a mixed-flow air to air membrane enthalpy exchanger with different configurations. (5th February 2020) - Albdoor, Ahmed K.; Ma, Zhenjun; Cooper, Paul
Highlights: The performance of a MEE with different flow configurations was evaluated. The moisture diffusivity and elastic modulus of five porous membranes were tested. Using appropriate flow patterns for two air streams can offer good performance. Abstract: This paper presents an experimental investigation and performance evaluation of a mixed-flow air to air membrane enthalpy exchanger with different flow configurations. The moisture diffusivity, water contact angle and elastic modulus of five porous membranes were first experimentally determined using a wet cup test method, a contact angle meter and the tensile test, respectively. The five porous membranes investigated consisted of two Polyvinylidene difluoride membranes with the mean pore diameters of 0.22 µm (PVDF22) and 0.45 µm (PVDF45) respectively, two Nylon membranes with 0.1 µm and 0.45 µm pore sizes respectively and one Polyethersulfone (PES) membrane with a 0.1 µm pore size. The optimal membrane was then identified and used to fabricate an enthalpy exchanger. Lastly, the performance of the enthalpy exchanger with different mixed-flow configurations was experimentally investigated. The results showed that the PVDF45 membrane offered the highest moisture diffusivity (1.91 × 10 −6  ± 2.42 × 10 −8 m 2 /s) with hydrophilic surface and a relatively high elastic modulus (4.97 × 10 8  ± 3.86 × 10 7 Pa). It was shown that the enthalpy exchanger with Z-shape flow of the supply air stream and И-shape flow of the exhaust air stream at an entrance ratio of 0.25 offered the best thermal performance as the sensible, latent and total effectiveness increased by 12.3%, 15.1% and 14.6% respectively, when the flow rate was 0.3  l/s, as compared to that of the pure cross flow. The same flow configuration was able to recover the highest energy among all configurations investigated.